Neoliberalism, Interrupted: Social Change and Contested Governance in Contemporary Latin America - GOODALE, Mark (ed.) (Stanford University Press, 2013)
Buku ini tentang perubahan sosial dan perebutan pemerintahan di Amerika Latin.